2016
DOI: 10.1186/s12883-016-0687-z
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of recurrent Guillain-Barré syndrome with normal cerebrospinal fluid protein levels: a case report

Abstract: BackgroundGuillain-Barré syndrome is an acquired polyradiculo-neuropathy, often preceded by an antecedent event. It is a monophasic disease but a recurrence rate of 1–6 % is documented in a subset group of patients. Patients with Guillain-Barré syndrome show cerebrospinal fluid albuminocytologic dissociation. Normal cerebrospinal fluid protein levels during both initial and recurrent episodes of Guillain-Barré syndrome is a rare occurrence and has not been described earlier in the literature.Case presentationT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…GBS is a medical emergency, which usually presents with acute onset, rapidly progressive, ascending paralysis [5]. Our patient presented with 2 weeks duration of symptoms.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…GBS is a medical emergency, which usually presents with acute onset, rapidly progressive, ascending paralysis [5]. Our patient presented with 2 weeks duration of symptoms.…”
Section: Discussionmentioning
confidence: 81%
“…Generally, cyto-albumin dissociation can be seen in 82-90 % of patients with GBS 10-14 days from the onset of the illness. But a normal CSF profile is found in 10% of GBS patients throughout the disease [5].…”
Section: Discussionmentioning
confidence: 98%
“…Review of available literature has not revealed potential mechanisms or differentials for this phenomenon. 6 7 …”
Section: Discussionmentioning
confidence: 99%
“…Although albuminocytologic dissociation is seen in 82% to 90% of patients with GBS by the end of the second week of illness, normal protein levels may still be present during the first week. [ 6 ] CSF albuminocytological dissociation is absent within the first week of symptom onset in more than half of the patients with GBS. Nerve conduction studies and CSF analyses are often inconclusive in the early stages of the disease, [ 7 ] and CSF can show a normal protein level in weak patients early in presentation.…”
Section: Discussionmentioning
confidence: 99%